Specific immune responses after BNT162b2 mRNA vaccination and COVID-19 infection - Arientová, Simona; Matúšková, Kateřina; Bartoš, Oldřich; Holub, Michal; Beran, Ondřej (Frontiers in Immunology, 2023)
Although vaccines against COVID-19 are effective tools in preventing severe disease, recent studies have shown enhanced protection after vaccine boosters. The aim of our study was to examine the dynamics and duration of both humoral and cellular responses following a threedose regimen of the BNT162b2 mRNA vaccine. In a longitudinal prospective study we enrolled 86 adults who received the BNT162b2 vaccine, 35 unvaccinated individuals with a history of mild COVID-19 and a control group of 30 healthy SARS-CoV-2 seronegative persons. We assessed the SARS-CoV-2-specific T cell responses and IgG production up to 12 months post the third BNT162b2 dose in 24 subjects. The vaccinated group had significantly higher IgG antibody levels after two doses compared to the convalescent group (p < 0.001).After the third dose, IgG levels surged beyond those detected after the second dose (p < 0.001). Notably, these elevated IgG levels were maintained 12 months post the third dose.After two doses, specific T cell responses were detected in 87.5% of the vaccinated group.Additionally, there was a significant decrease before the third dose. However, post the third dose, specific T cell responses surged and remained stable up to the 12-month period. Our findings indicate that the BNT162b2 vaccine induces potent and enduring humoral and cellular responses, which are notably enhanced by the third dose and remain persistant without a significant decline a year after the booster. Further research is essential to understand the potential need for subsequent boosters.